ESTIMATION OF HOMOGENEITY STAGE OF BIOMASS MIXTURES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Components of mixtures .have to be in required proportion and homogeneous mixed to provide good quality (density, durability, and burning properties) of briquettes or pellets. For estimation of proportion of components and homogeneity several methods can be used: density o f briquettes; durability of briquettes; proportion of the components in a determined volume; visual estimation. Visual estimation is a picture analyzing when quality tests through processing of digital pictures are performed. Standard deviation of the visual estimation of area occupied by mixture component particles does not exceed 5%. Standard deviation of the distance between straw particles has good correlation with increased peat proportion. Coefficient of determination is 0.98.